Strategic Foresight and Entrepreneurial Orientation in Enhancing Business Adaptability for Navigating Uncertainty in Food and Beverage SMEs - Enny Noegraheni Hindarwati; Agus Rahayu; Vanessa Gaffar; Lili Adi Wibowo (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Rising market, technological, and environmental uncertainties challenge Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector, making strategic foresight and entrepreneurial orientation essential for adaptability and competitiveness. This study aims to examine the effects of strategic foresight and entrepreneurial orientation on business adaptability in navigating uncertainty among food and beverage MSMEs in Jakarta. A quantitative approach with a cross-sectional survey design was employed. Data were collected from 100 MSME owners or managers using a structured questionnaire and analyzed using structural equation modeling–partial least squares. The results indicate that strategic foresight has a significant positive effect on business adaptability, while entrepreneurial orientation strengthens innovation, proactiveness, and organizational resilience. Furthermore, business adaptability is found to mediate the relationship between strategic foresight and the ability of MSMEs to navigate business uncertainty. These findings highlight the importance of integrating foresight and entrepreneurial orientation as dynamic capabilities to enhance MSME resilience. This study contributes theoretically to the dynamic capabilities perspective and provides practical insights for business practitioners and policymakers in strengthening the adaptive capacity of food and beverage MSMEs amid an increasingly uncertain business environment.